GmWRKY21, a Soybean WRKY Transcription Factor Gene, Enhances the Tolerance to Aluminum Stress in Arabidopsis thaliana - Han, Zhenzhen; Wang, Jinyu; Wang, Xinxin; Zhang, Xijia; Cheng, Yanbo; Cai, Zhandong; Nian, Hai; Ma, Qibin (Frontiers in Plant Science, 2022)
The WRKY transcription factors (TFs) are one of the largest families of TFs in plants and play multiple roles in plant growth and development and stress response. In this study, GmWRKY21 encoding a WRKY transcription factor was functionally characterized in Arabidopsis and soybean. The GmWRKY21 protein containing a highly conserved WRKY domain and a C2H2 zinc-finger structure is located in the nucleus and has the characteristics of transcriptional activation ability. The GmWRKY21 gene presented a constitutive expression pattern rich in the roots, leaves, and flowers of soybean with over 6-fold of relative expression levels and could be substantially induced by aluminum stress. As compared to the control, overexpression of GmWRKY21 in Arabidopsis increased the root growth of seedlings in transgenic lines under the AlCl3 concentrations of 25, 50, and 100 μM with higher proline and lower MDA accumulation. The results of quantitative real-time polymerase chain reaction (qRT-PCR) showed that the marker genes relative to aluminum stress including ALMT, ALS3, MATE, and STOP1 were induced in GmWRKY21 transgenic plants under AlCl3 treatment. The stress-related genes, such as KIN1, COR15A, COR15B, COR47, GLOS3, and RD29A, were also upregulated in GmWRKY21 transgenic Arabidopsis under aluminum stress. Similarly, stress-related genes, such as GmCOR47, GmDREB2A, GmMYB84, GmKIN1, GmGST1, and GmLEA, were upregulated in hair roots of GmWRKY21 transgenic plants. In summary, these results suggested that the GmWRKY21 transcription factor may promote the tolerance to aluminum stress mediated by the pathways regulating the expression of the acidic aluminum stress-responsive genes and abiotic stress-responsive genes.